Understanding the Activity and Stability of Vanadium Oxynitride Thin Films for N2 Reduction to Ammonia by Combining Theory and Operando Measurements - Wang, Jinchao; Kuorak, Johan Michael; Priamushko, Tatiana; Gunnarsdóttir, Anna B.; Stojanovski, Kevin; K. Tryggvason, Tryggvi; Lewin, Erik; Magnus, Fridrik; Ingason, Árni S.; Hanifpour, Ása; Höskuldsson, Árni B.; Cherevko, Serhiy; et al. (Small Methods, 2025)
The electrocatalytic nitrogen reduction reaction (NRR) to ammonia offers a sustainable alternative to the Haber-Bosch process. Vanadium oxynitrides (VON) have been proposed in simulations as promising NRR catalysts via the Mars-van Krevelen mechanism. However, investigating nitrogen-containing materials for NRR is challenging due to possible instability-driven nitrogen leaching. Hence, well-designed and rigorous experiments are crucial to evaluate the stability and activity of such materials under NRR operation. To address this, operando measurements are conducted on VON thin films to assess metal dissolution (stability) and NH3 production (activity). This study introduces a modified stability number (S-number) to quantify ammonia produced per dissolved metal ions. VO0.19N0.81 exhibits an S-number over four times higher in N2 than in Ar, indicating improved stability under NRR conditions. While Faradaic efficiencies remain low (1–2%), steady ammonia production is observed for over 1.5 h, suggesting potential catalytic activity. Furthermore, the simulations indicate refilling of surface vacancies is more favorable when lattice oxygen is present, offering a mechanistic understanding of enhanced stability of VON in N2 compared to Ar. The study paves the way for the development of more stable catalysts and introduces new metrics into the NRR field to facilitate the reporting of trustworthy results.
CRIS-Team Scopus Importer:2025-11-28
Keywords: electrocatalyst stability; Mars−van Krevelen mechanism; nitrogen reduction reaction; operando studies; transition metal oxynitride